Recovery of Renal Function Under PSMA Mediated Radioligand Therapy of Advanced Metastasized Castration Resistant Prostate Cancer. (September 2019) - Ries, Martin; Khreish, Fadi; Berchem, Guy; Ezziddin, Samer
Abstract : Abstract: Radioligand therapy targeting prostate specific membrane antigen (PSMA-RLT) is becoming increasingly important in palliative care of metastasized castration resistant prostate cancer (mCRPC) as a highly effective and low toxicity therapy option. In addition to its overexpression in prostate cancer cells, PSMA is also physiologically expressed in the kidneys which is raising concerns over dose related nephrotoxicity of PSMA-RLT. We describe potential positive short-term effects of PSMA-RLT on renal function with marked recovery of a pretreatment compromised kidney.